2018
DOI: 10.1249/jsr.0000000000000505
|View full text |Cite
|
Sign up to set email alerts
|

Exercise is Medicine for Concussion

Abstract: Sport-related concussion (SRC) is a physiological brain injury that produces cerebral and systemic effects, including exercise intolerance. Exercise intolerance after concussion is believed to be the result of autonomic nervous system (ANS) dysfunction. Ventilation is inappropriately low for the level of exercise intensity, raising arterial carbon dioxide (PaCO2) levels. Elevated PaCO2 increases cerebral blood flow (CBF) out of proportion to exercise intensity, which is associated with symptoms that limit exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(129 citation statements)
references
References 73 publications
4
122
0
3
Order By: Relevance
“…(1) that acute, short duration mild-to-intense exercise testing (HR = 110 bpm-170 bpm) can be performed safely in the days (D2, D4, D7) immediately following the diagnosis of concussion; and (2) that physiological measures can be easily collected and can be used to add to our understanding of the pathophysiological effects of concussion. This has important implications for treatment strategies, as current research suggests that sport-related concussion or mTBI is a physiological brain injury (McCrory et al, 2017;Leddy et al, 2018), and that concussion testing can potentially differentiate the type of mTBI (Ellis et al, 2015). Furthermore, our data support recent reports that physical exercise can be used safely when assessing recently concussed athletes within the first week post-injury in a controlled laboratory environment (Leddy et al, 2016a(Leddy et al, , 2017Haider et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…(1) that acute, short duration mild-to-intense exercise testing (HR = 110 bpm-170 bpm) can be performed safely in the days (D2, D4, D7) immediately following the diagnosis of concussion; and (2) that physiological measures can be easily collected and can be used to add to our understanding of the pathophysiological effects of concussion. This has important implications for treatment strategies, as current research suggests that sport-related concussion or mTBI is a physiological brain injury (McCrory et al, 2017;Leddy et al, 2018), and that concussion testing can potentially differentiate the type of mTBI (Ellis et al, 2015). Furthermore, our data support recent reports that physical exercise can be used safely when assessing recently concussed athletes within the first week post-injury in a controlled laboratory environment (Leddy et al, 2016a(Leddy et al, , 2017Haider et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…To our knowledge this is the first study to systematically evaluate the physiological effects of repeated exercise tests using mild-to-intense exercise intensity (HR∼ 110-170 bpm) performed within 2-days (D2) after the medical diagnosis of sport-related concussion in high-performance athletes. Based on the growing body of literature in this area, moderate-to-intense exercise testing can be performed in concussed athletes safely, but most studies were performed more than a week after injury Ellis et al, 2015;Hinds et al, 2016;Leddy et al, 2016bLeddy et al, , 2018Haider et al, 2019;Morissette et al, 2019). Using an evidence-based approach, similar to our study, Leddy et al (2011Leddy et al ( , 2017 developed the Buffalo Concussion Treadmill and Bike Tests to specifically evaluate symptom limitations in post-concussion syndrome (PCS) patients and showed that concussed athletes assessed on average of 33 weeks (6-36 weeks) post-injury could reliably differentiate physiological dysfunction and quantify exercise capacity in PCS patients.…”
Section: Basis Of Physiological Concussion Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…A formal symptom-limited aerobic exercise programme has been shown to be safe and improve resolution of persistent symptoms compared with controls and should be considered in athletes with symptoms lasting longer than expected 78–80. The Buffalo Concussion Exercise Treatment Protocol, a progressive subsymptom threshold aerobic exercise programme based on systematically establishing the level of exercise tolerance on the Buffalo Concussion Treadmill Test, is the most studied controlled exercise programme 81. It is ideal for those with persistent postconcussive symptoms to be evaluated by a provider or multidisciplinary team with expertise in complicated concussion management.…”
Section: Management Of Concussionmentioning
confidence: 99%
“…Current practice has shifted to support subsymptom‐level exercise after 24‐48 hours of rest and active rehabilitation if there is delayed recovery, although the optimal timing following injury for initiation of exercise remains unknown 2,31,68 . Safety and efficacy of early exercise has been previously demonstrated with no long‐term adverse effects attributed to transient symptoms exacerbation that may occur during post‐injury exercise 73‐77 …”
Section: Return To Learn and Return To Play (Rtl/rtp) Post‐mtbimentioning
confidence: 99%